“Potential Use of Mango Waste and Microalgae Spirulina sp. for Bioelectricity Generation“ - De La Cruz-Noriega M. (2022)
“Potential use of organic waste and microalgae generates bioelectricity and thereby reduces harmful effects on the environment. These residues are used due to their high content of electron-generating microorganisms. However, so far, they have not been used simultaneously. Therefore, this research uses mango waste and microalgae Spirulina sp. in double-chamber microbial fuel cells to generate bioelectricity. The cells were made at a laboratory scale using zinc and copper electrodes, achieving a maximum current and voltage of 7.5948 ± 0.3109 mA and 0.84546 ± 0.314 V, with maximum electrical conductivity of the substrate being 157.712 ± 4.56 mS/cm and an optimum operating pH being 5.016 ± 0.086. The cells showed a low internal resistance of approximately 205.056 ± 25 Ω, and a maximum power density of 657.958 ± 21.114 mW/cm2 at a current density of 4.484 A/cm2 . This research provides an excellent opportunity for mango farmers and exporting and importing companies because they can use their own waste to reduce their electricity costs when this prototype is brought to a large scale.“